PENGARUH VARIASI VOLUME ETANOL PADA PEMBUATAN TINTA SPIDOL WHITEBOARD MENGGUNAKAN PEWARNA EKSTRAK KULIT BUAH RAMBUTAN - Ida Ayu Lestari; Fitriyana Fitriyana; Yuli Padmawati (Politeknik Negeri Samarinda, 2021)
The rambutan peel will only be discarded after the fruit is eaten. Rambutan peel contains tannin compounds which are used as dyes in the paint and ink industries. The tannin compounds contained in the rambutan peel can also be used as a dye base material in the manufacture of ink markers. The purpose of this study is to determine the effect of ethanol volume variations on the characteristics of whiteboard markers with dye base material from rambutan peel extract to meet the Indonesia National Standard (SNI) for ink 06-1567-1999 which is safer for health. Making ink markers was carried out in several stages, namely, preparation of rambutan peel, extraction of rambutan peel, and mixing ink ingredients, among others, 3.5 g of arabic gum, 7 mL of aquades, 1 g of skin extract rambutan fruit, 10 drops of 10% FeCl3 solution, 0.2 g PEG 400, and 96% ethanol. Ethanol volume was varied as follows: 2 mL, 4 mL, 6 mL, 8 mL, and 10 mL. Based on the results of the analysis, the best results were obtained on the variation of 10 mL ethanol volume with a density of 0.9431 g/mL and a viscosity of 1.1169 cP which have met the SNI for ink 06-1567-1999. In addition, ink has dry time of 2.20 minutes, a smell like raw materials and purplish black colour.